Etablering av höstvete med reducerad jordbearbetning - Åkesson, Elias (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
The payment for produced grain is constantly going down in price. It is important for farmers to become more effective in cultivating more land in a shorter time perspective. At the same time we have to calculate with the risk of getting lowered subsidies from the EU. This is why I would like to find out the possibilities for establishing winter wheat without ploughing. I hope to find a difference in the number of plants due to different soil preparations. With this experiment I expect to find out whether I can establish winter wheat at a lower cost, with the same numbers of plants per square meter. The experiment consists of four different kinds of cultivation. The four different kinds of cultivation take place in eight squares each. I have in every one of these thirty-two squares counted the number of plants per square meter in two smaller test circles. These circles had a diameter of approximately forty centimetres. The winter wheat experiments I've studied show a lower cost for crop-establishing when you reduce the cultivation. Lower costs for the establishing of the crop allow you to accept a lower yield. My experiments show that ploughing is positive for the plant establishing. The results show a very small and not significant difference in the number of plants per square meter between the different experiments. Since the difference was small and it seems not so important for the yield, so economically you might prefer no ploughing.